Diagnosis and therapy of pemphigus - consensus of Polish Dermatological Society - Cezary Kowalewski; Marian Dmochowski; Waldemar Placek; Elżbieta Waszczykowska; Roman Nowicki; Iwona Flisiak; Rafał Czajkowski; Ligia Brzezińska-Wcisło; Jacek Szepietowski; Andrzej Kaszuba; Katarzyna Woźniak (Termedia Publishing House, 2014)
Pemphigus is an acantholytic bullous disease with a potentially fatal course. The laboratory diagnosis of pemphigus is based on direct immunofluorescence showing the presence of the in vivo bound IgG in intercellular spaces of the epidermis in skin biopsy. For determining the clinical subtypes of pemphigus serum immunological studies allowing characterization of the target antigen(s) are obligatory. Treatment of pemphigus with prednisone at an initial dose of 1-1.5 mg/kg in combination with azathioprine is currently recommended by most dermatologists as well as by the European Expert Group as the therapy of choice in typical cases, whereas other immunosuppressive agents, biological drugs, and intravenous immunoglobulins should be considered in refractory cases and rare subsets of pemphigus.